Compact Circularly Polarized Patch Antenna for WiMAX Applications with Improved Impedance Bandwidth and Axial Ratio - Swetha, R.; Anjaneyulu, L. (Engineering, Technology & Applied Science Research, 2020)
This paper presents a circularly polarized microstrip patch antenna for WiMAX (Worldwide Interoperability for Microwave Access) application with improved impedance bandwidth and axial ratio compared to the existing designs. The antenna is designed at a resonant frequency of 3.56GHz on the FR4 substrate with 2mm thickness. The dimensions of the antenna are 0.35λo×0.35 λo×0.023λo and it is fed through a probe feed. An impedance bandwidth of 360MHz (10.11%) in the frequency range of 3.44GHz−3.8GHz, with a gain of 3.16dBi, axial ratio bandwidth of 1.9% (3.56GHz−3.63GHz) and VSWR<2 are obtained.